2017
DOI: 10.1080/2374068x.2017.1330856
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of components manufactured from a range of materials, fabricated using PolyJet technology

Abstract: With advances in additive manufacturing, particularly in the area of three dimensional (3D) printing, it is becoming possible to generate small quantities of functional components. As with all manufacturing technologies, the ability to reproducibly generate parts with defined dimensional accuracy and surface finish is of key importance. This work characterises the ability of one such technology, PolyJet 3D printing, to produce such parts. In order to characterise the output from the manufacturing technique, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…White and Tango Plus has been used to represent bone in other 3D-printed medical applications such as the thorax and have been used to substitute hard and soft tissues in models (35,48,49). This adds to the tactile experience of the trainees.…”
Section: Discussionmentioning
confidence: 99%
“…White and Tango Plus has been used to represent bone in other 3D-printed medical applications such as the thorax and have been used to substitute hard and soft tissues in models (35,48,49). This adds to the tactile experience of the trainees.…”
Section: Discussionmentioning
confidence: 99%
“…In MJ, dimensional accuracy of printed parts depends mostly on polymerization speed and photocurable resin material viscosity [ 32 ]. Kechagias et al investigated the effect of layer thickness, surface finish setting (matte or glossy) and model scale factor on dimensional accuracy of internal and external features produced by MJ.…”
Section: Process and Materialsmentioning
confidence: 99%
“…Kent et al investigated the effect of build orientation on surface roughness and dimensional accuracy of MJ printed parts with four different materials. They found that build orientation has a very high impact on these measurements, but the results were not fully consistent with each other [ 32 ]. Haghighi et al stated that a horizontal build resulted in better dimensional accuracy than vertical builds [ 44 ].…”
Section: Process and Materialsmentioning
confidence: 99%
“…Working principle of Objet260 Connex PolyJet process is illustrated in Figure 3. 144,159 In this machine, photopolymer resins are selectively deposited onto the build tray as per sliced 2D profile by eight print heads (four for model material, another four for support material) through multiple nozzles then it is immediately solidified by ultraviolet light. Assembly of jetting heads moves in X and Y axis it includes one leveling roller on right hand side and ultraviolet lamps on both ends.…”
Section: Ophthalmic Case Examplesmentioning
confidence: 99%